Commonalities between Perception and Cognition - Tacca, Michela C. (Frontiers in Psychology, 2011)
Perception and cognition are highly interrelated. Given the influence that these systems exert on one another, it is important to explain how perceptual representations and cognitive representations interact. In this paper, I analyze the similarities between visual perceptual representations and cognitive representations in terms of their structural properties and content. Specifically, I argue that the spatial structure underlying visual object representation displays systematicity—a property that is considered to be characteristic of propositional cognitive representations. To this end, I propose a logical characterization of visual feature binding as described by Treisman’s Feature Integration Theory and argue that systematicity is not only a property of language-like representations, but also of spatially organized visual representations. Furthermore, I argue that if systematicity is taken to be a criterion to distinguish between conceptual and nonconceptual representations, then visual representations, that display systematicity, might count as an early type of conceptual representations. Showing these analogies between visual perception and cognition is an important step towards understanding the interface between the two systems. The ideas here presented might also set the stage for new empirical studies that directly compare binding (and other relational operations) in visual perception and higher cognition.